A user-guide for polymer purification using dialysis. Issue 1 (29th November 2022) - Schuett, Timo; Anufriev, Ilya; Endres, Patrick; Stumpf, Steffi; Nischang, Ivo; Hoeppener, Stephanie; Zechel, Stefan; Schubert, Ulrich S.; Geitner, Robert
Abstract : Dialysis diffusion kinetics are performed via in situ NMR spectroscopy for numerous different raw polymeric solutions to result in a general guideline for polymer purification using dialysis. Abstract : Dialysis diffusion kinetics are investigated via in situ NMR spectroscopy for numerous different raw polymeric solutions to result in a general guideline for polymer purification using dialysis. In several approaches, a polymer was on purpose contaminated with its respective monomer, regenerated conducting conventional dialysis and monitored online utilizing in situ NMR spectroscopy. Consequently, polymer type and molar mass, monomer type, molar mass cut-off of the dialysis tubing and type of solvent were varied resulting in 29 different purification approaches and over 40 000 NMR-spectra. As a result, several major parameters were identified affecting the purification process significantly such as the chosen solvent, viscosity and alpha value. On the contrary, parameters such as dialysis tubing molar mass cut-off and molar mass of the polymer did not affect the purification in a significant manner. Furthermore, physical properties such as density, viscosity, alpha value, and dipole moment of the ingredients were combined in a principal component analysis in order to identify the most important parameters.